(untitled) (Bangladesh Journal of Medical Physics, 2021)
Focused Impedance Method (FIM) is a new and simple technique of electrical bio-impedance that provides an opportunity for localized measurement down to reasonable depths of the body surface using skin surface electrodes. Conceived by one of the authors (KSR) and developed in Bangladesh by a group led by him, FIM has potential applications in physiological study and in the detection or diagnosis of diseases and disorders. Being a simple technique, it is particularly suitable for low and medium income countries (LMIC). To obtain long term benefit from any technology it is necessary that the technology is understood and developed indigenously, particularly under the limitation of a resource limited country. Indigenous development also allows for further improvisation, innovation, and application in future. This paper presents the indigenous design and development of the electronic instrumentation necessary for the implementation of six electrode version of Focused Impedance Method (FIM-6) in Nepal. The work involved basic characterization of the necessary circuit blocks developed through experimental validation. In particular, the design of isolating ferrite transformers required for the instrumentation posed a challenge which was solved limiting the range of the instrumentation to range variations encountered in practice on the human body, for which initial experiments were carried out on a live human subject. This led to a simplified design. The values obtained using the developed circuitry appears to give reasonable accuracy and would be useful for further implementation of the instrumentation using PCBs. However, further work can also be taken to improve the design of the current source used and of the transformers. Thus this work satisfies the initial requirement of attempting indigenous development of the FIM technique in an LMIC like Nepal. Bangladesh Journal of Medical Physics Vol.14 No.1 2021 P 1-15